Correlates of Reported Use and Perceived Helpfulness of Calorie Information in Restaurants Among U.S. Adults. Issue 4 (March 2016) - Oh, April; Nguyen, Anh Bao; Patrick, Heather
Purpose: This study reports correlates in reported use and helpfulness of calorie information, when available, in restaurants on a national scale in the United States for demographic behavioral and health-related conditions. Design: This study is a secondary data analysis of the 2013 National Cancer Institute's Health Information National Trends Survey data. Setting: United States. Subjects: Adults ( n = 3407). Measures: Menu labeling use and helpfulness; behavior change attempts; reported fruit, vegetable, and soda consumption; weight status; and chronic health conditions. Analysis: Trends were identified in weighted logistic and linear regression models. Results: U.S. adults who intended to lose weight (odds ratio [OR] = 5.01 [95% confidence interval 2.96, 8.46]), increase fruit (OR = 1.10 [.66, 1.84]) or vegetable consumption (OR = 2.25 [1.32, 3.83]), or reduce soda consumption (OR = 1.67 [1.11, 2.51]) were more likely to report using menu-labeling information when available. More women reported calorie information was helpful when ordering ( p < .05). Racial/ethnic and socioeconomic status disparities were identified in use (non-Hispanic [NH] blacks vs. NH whites OR = .43 [.25, .74]) and helpfulness (NH blacks vs. NH whites β = –.06 [–.44, .32]). Conclusion: Findings highlight potential subgroups to target for communication and education efforts regarding use of calorie information in restaurants. Following publication of final rules for federal menu-labeling legislation and implementation, further surveillance of public response to this information may inform message framing and educational interventions to promote use of calorie information on menu boards.